PENGARUH UMPAN NABATI, HEWANI DAN CAMPURAN KEDUANYA TERHADAP HASIL TANGKAPAN UDANG GALAH (Macrobracium rosenbergii) - Brown, Arthur; Syofyan, Irwandy (Jurnal Perikanan dan Kelautan, 2010)
Field Experiment was carry out to study the effect of vegetable and animalbase baits and combination of both on shrimp catches (Macrobrachiumrosenbergii de Man). This Fishing Experiment was using a simple randompattern, with three treatments as following U1 =Bran, U2=Fish Flour, U3=Mixing of Bran and Fish Flour. This experiment was undertaken from 7th till 13thjuli 2009.The treatments effected on number and weight of catches shrimp differentlyas the fish was bring highest catches, followed by mixed bait and the lowestcatches is bran in respectively were 16 shrimps (380 grams), 12 shrimps ( 240grams) and 10 shrimps (170 grams).